ON THE OCCURRENCE OF NEMIPTERUS METOPIAS (BLEEKER, 1852) (NEMIFTERIDAE, PISCES) FROM THE SOUTH WEST COAST OF INDIA - Mohan, Madan; Gopakumar, G (Indian Journal of Fisheries, 2011)
The species of Nemipterus so far reported to occur in the seas around India are, Nemipterus margtnatus (Valenoiennies), N. hexodon (Quoy >and Gaimard), N. japonicus (Bloch), N. luteus (Schneider), N. mesoprion (Bleeker), N. tolu (Val.) and N. delagoae Smith (Day 1878, Weber and De Beaufort 1936, and Muilhy Mas). The present authors collected five specimens of Nemipterus metopias (Sleeker) the occurrence of which has not been recorded so far from Indian waters, from Vizhinjam during February 1980 from the catches by hooks and lines.